Hematopoietic stem and progenitor cell membrane-coated vesicles for bone marrow-targeted leukaemia drug delivery - Li, Jinxin; Wu, Honghui; Yu, Zebin; Wang, Qiwei; Zeng, Xin; Qian, Wenchang; Lu, Siqi; Jiang, Lingli; Li, Jingyi; Zhu, Meng; Han, Yingli; Gao, Jianqing; et al. (Nature communications, 2024)
Leukemia is a kind of hematological malignancy originating from bone marrow, which provides essential signals for initiation, progression, and recurrence of leukemia. However, how to specifically deliver drugs to the bone marrow remains elusive. Here, we develop biomimetic vesicles by infusing hematopoietic stem and progenitor cell (HSPC) membrane with liposomes (HSPC liposomes), which migrate to the bone marrow of leukemic mice via hyaluronic acid-CD44 axis. Moreover, the biomimetic vesicles exhibit superior binding affinity to leukemia cells through intercellular cell adhesion molecule-1 (ICAM-1)/integrin β2 (ITGB2) interaction. Further experiments validate that the vesicles carrying chemotherapy drug cytarabine (Ara-C@HSPC-Lipo) markedly inhibit proliferation, induce apoptosis and differentiation of leukemia cells, and decrease number of leukemia stem cells. Mechanically, RNA-seq reveals that Ara-C@HSPC-Lipo treatment induces apoptosis and differentiation and inhibits the oncogenic pathways. Finally, we verify that HSPC liposomes are safe in mice. This study provides a method for targeting bone marrow and treating leukemia. Effective delivery of drugs to bone marrow has potential for leukemia treatment. Here the authors report the delivery of chemotherapy drug Ara-C with HSPC cell membrane derived-biomimetic vesicles, which target leukemia stem cells thereby effectively inhibit its progression.